Nurses' attitudes and stress related to perinatal bereavement care in Korea: a cross-sectional survey - Eunhui Kim; Hae Won Kim (Korean Society of Women Health Nursing, 2022)
Purpose A descriptive correlational survey was conducted to examine nurses' attitudes and stress related to perinatal bereavement care (PBC) and their relationships, with the ultimate goal of improving nurses' capabilities related to PBC. Methods Korean nurses (N=136) who had experienced perinatal death at least once were recruited from seven hospitals. Data were analyzed using descriptive statistics. The Korean version of Nurses' Attitudes towards Perinatal Bereavement Support was assessed in terms of three subdomains (attitudes to PBC, importance of policies related to PBC, and importance of training related to PBC), and nurses' stress was measured. Results The participants gave high scores for the attitude-related items of "giving sufficient time to bereaved parents to mourn for their dead baby" (4.54 points) and "nurses should treat bereaved parents with respect and dignity" (4.51 points), and they perceived a high level of importance for the policy-related items of "every staff member in the hospital should understand the policies relevant for PBC" and "when nurses feel emotional exhaustion, they should seek support" (4.58 points). Nurses' attitude toward PBC was associated with the perceived importance of policies (r=.40, p<.001), the perceived importance of PBC-related training (r=.61, p<.001), and stress related to PBC (r=.29, p<.001). Nurses' perceived importance of PBC-related training was associated with stress related to PBC (r=.38, p<.001). Conclusion Establishing hospital policies related to PBC and providing PBC training for nurses could positively affect nurses' attitudes toward PBC. A stress management program for nurses could reduce the stress caused by PBC.